Development of ready-to-drink sweet potato leaf (Ipomea batatas) extract (RTD SPLE) in doy packs - Del Rosario, Jocelle Ramilo; Rustia, Abigail S. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
The study aimed to develop a ready-to-drink sweet potato (Ipomea batatas) leaf extract (RTD SPLE) in doy packs using response surface methodology (RSM). Statistical models were generated to establish the effects of formulation and process parameters on the physicochemical and consumer acceptability responses of RTD SPLE. The amount of calamansi-honey concentrate (CHC) (ml/100 ml SPLE) and processing time (min) were optimized to produce an RTD SPLE in doy pack with a final pH of 2.77-4.5 and has an overall acceptability score of 7. Verification experiments were conducted to validate the accuracy of the predictive models. The RSM models showed that amount of CHC and the interaction between amount of CHC and processing time have significant (p<0.05) effects on pH. In addition, overall acceptability was significantly (p<0.05) affected by amount of CHC. Results of the optimization showed that optimal combinations were: (1) mature Inubi with 10.59-10.64 ml of CHC processed for 2 min; (2) young Inubi with 10.95-11.11 ml CHC processed for 2 min; and (3) young Kinerots with 10.86-11.50 ml CHC processed for 2 min. Verification experiments proved that the statistical models accurately predicted the responses. The findings indicate that sweet potato leaves may be used in the production of a RTD beverage.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Sweet potato leaves -- Processing; Vegetable juices